2022
DOI: 10.1002/alz.12543
|View full text |Cite
|
Sign up to set email alerts
|

Increased RyR2 open probability induces neuronal hyperactivity and memory loss with or without Alzheimer's disease–causing gene mutations

Abstract: Introduction Neuronal hyperactivity is an early neuronal defect commonly observed in familial and sporadic Alzheimer's disease (AD), but the underlying mechanisms are unclear. Methods We employed a ryanodine receptor 2 (RyR2) mutant mouse model harboring the R4496C+/– mutation that markedly increases the channel's open probability (Po) to determine the impact of increased RyR2 activity in neuronal function without AD gene mutations. Results Genetically increasing RyR2 Po induced neuronal hyperactivity in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…However, while behavioral states likely alter network performance, this does not necessarily obviate before/after comparisons in experiments using acute INI or L‐VGCC modifiers for mechanistic investigations. Further, little to no change in the mean frequency of Ca 2+ transients and the number of hyperactive neurons in the hippocampal CA1 field has been detected between awake and anesthetized mice using in vivo 2P Ca 2+ imaging (Yao et al, 2022). While amplitude differences in cortical hemodynamic imaging and neurovascular unit (NVU) activation (i.e., oxyhemoglobin and deoxyhemoglobin) and increases in network synchronicity are seen using anesthesia, the direction of change in response to whisker stimulation is unaffected (Martin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, while behavioral states likely alter network performance, this does not necessarily obviate before/after comparisons in experiments using acute INI or L‐VGCC modifiers for mechanistic investigations. Further, little to no change in the mean frequency of Ca 2+ transients and the number of hyperactive neurons in the hippocampal CA1 field has been detected between awake and anesthetized mice using in vivo 2P Ca 2+ imaging (Yao et al, 2022). While amplitude differences in cortical hemodynamic imaging and neurovascular unit (NVU) activation (i.e., oxyhemoglobin and deoxyhemoglobin) and increases in network synchronicity are seen using anesthesia, the direction of change in response to whisker stimulation is unaffected (Martin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests that the mutation found in the two subjects may have altered the RyR-2 channel function in neurons, with consequences on the Ca 2+ homeostasis during the aging trajectory of the brain, contributing to the synaptic loss and the development of dementia. Very recently, it has been demonstrated that increased RyR2 open probability induces neuronal hyperactivity and memory loss, two common manifestations of AD and AD progression [ 56 ]. Moreover, pharmacological treatment aimed to reduce RyR2 open time has been demonstrated to rescue AD-related deficits in mouse models, suggesting this molecular pathway as a potential target for addressing AD [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of dantrolene, either alone or in combination with immunotherapy, might also be considered for the treatment of AD. Additionally, post-translation modification of the RyR2 or RyR2 mutations have been linked to AD [ 186 , 187 ]. More specifically, Yao et al reported that mice carrying the RyR2-R4496C mutation, which increases the open probability of the channel, displayed neuronal hyperactivity and impaired learning and memory formation.…”
Section: Similarities Between Ad and Wsmentioning
confidence: 99%
“…More specifically, Yao et al reported that mice carrying the RyR2-R4496C mutation, which increases the open probability of the channel, displayed neuronal hyperactivity and impaired learning and memory formation. Similarly, increasing the open probability of RyR2 in 5xFAD mice exacerbated the onset of these symptoms [ 187 ]. Hence, it would be interesting to assess whether patients with RyR2 mutations or other channelopathies are at risk of not only developing AD but also exhibiting features that resemble WS.…”
Section: Similarities Between Ad and Wsmentioning
confidence: 99%